2015
DOI: 10.14202/vetworld.2015.888-891
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and effects of nano mineral particle feeding in livestock: A review

Abstract: Nano minerals are widely used in diversified sectors including agriculture, animal, and food systems. Hence, their multiple uses provoke the production of nanomaterials at the laboratory level, which can be achieved through physical, chemical or biological methods. Every method is having its own merits and demerits. But keeping all in mind, chemical methods are more beneficial, as uniform nano-sized particles can be produced, but the use of corrosive chemicals is the main demerits. When it comes to environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 27 publications
(33 reference statements)
1
65
0
Order By: Relevance
“…Thus, reducing the size of minerals to nanoscale may increase their absorption and utilization. The added advantage is nanoparticles can efficiently be synthesized by using physical, chemical, or biological methods which are cheap and easy (Swain, Rajendran, Rao, & Dominic, ). Recently, researchers have found that mineral nanoparticles have a positive effect on the performance of broilers (Ahmadi, Ebrahimnezgad, Ghiasi ghalekhandi, & Maheri, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reducing the size of minerals to nanoscale may increase their absorption and utilization. The added advantage is nanoparticles can efficiently be synthesized by using physical, chemical, or biological methods which are cheap and easy (Swain, Rajendran, Rao, & Dominic, ). Recently, researchers have found that mineral nanoparticles have a positive effect on the performance of broilers (Ahmadi, Ebrahimnezgad, Ghiasi ghalekhandi, & Maheri, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results pertaining to values of minerals in the tibia are in agreement with those of Hassan et al (2016) who noted that feeding broiler chicks diets containing 0.44% of NDCP decreased the excreted Ca and P by about 51 and 46%, respectively comparing to the control diet. Swain et al (2015) reported that Nano minerals are having a great potential even at very lower doses than the conventional organic and inorganic sources. Nano form of minerals supplementation increases the surface area which possibly could increase absorption and utilization leading to reduction in the quantity of supplements and ultimately reduction in mineral excretion.…”
Section: Calcium and Phosphorus Excretion And Retentionmentioning
confidence: 99%
“…It also offers potential advantages in supporting research in many areas (nanoproteomics, medicine, diagnostics, etc.) of life sciences [18,19]. Copper is one of the essential trace mineral elements in the animal body, which plays an important role in growth and development [20].…”
Section: Introductionmentioning
confidence: 99%